Cloud Computing and Business Process Management: Possibilities, Challenges, New Concepts - Agnieszka BITKOWSKA; Damian DZIEMBEK; Tomasz GZIK (Communications of International Proceedings, 2022)
Modern companies must constantly evolve, adapting to a turbulently changing environment. This evolution, determined by the very rapid development of technology and the possibility to use it, implies new forms of doing business, customer contact, service provision and product delivery. Business models and practices that have worked so far are no longer able to provide an adequate framework for maintaining effective and efficient business operations. Business process management is a response to, among other things, the increasing turbulence of the business environment and the individualization of customer needs and expectations. A dynamically developing and widely used model for the provision and use of IT solutions is cloud computing. Business process management using cloud computing is a solution that can help service companies face the accompanying challenges. The article presents the practical possibilities of business process management using cloud computing, the challenges and the way forward. As a first step, the article presents the potential of business process management using cloud computing in the context of enterprise needs. This is followed by an explanation of the basic concepts and a presentation of the practical possibilities of business process management using cloud computing services. The final part of the article presents the directions of development of business process management in the calculation cloud and the concept of a new service: Business Process Management as a Service.
Keywords: Business Process Management; Cloud Computing; Cloud Business Process Management; Business Process Management as a Service; Business Process Management System as a Service; Process of Business Process Management as a Service; BPM; BPMaaS; BPMSaaS; PoBPMaaS; BPaaS